China’s Belt and Road Initiative as a Strategy for Hegemonic Contestation in the Indo-Pacific Region - Sitompul, Martua (Journal Of Management Analytical and Solution (JoMAS), 2025)
This article examines China's Belt and Road Initiative (BRI) as a strategic instrument in its efforts to challenge the existing hegemonic order in the IndoPacific region. Amid growing geopolitical rivalry, particularly with the United States and its allies, China has employed the BRI not merely as an economic development scheme, but as a tool of influence projection, regional integration, and soft power consolidation. Using a qualitative-descriptive approach and critical geopolitical analysis, this study explores how China’s BRI projects ranging from infrastructure development to digital connectivity are reshaping regional power dynamics. The research finds that China’s approach blends economic diplomacy with strategic interest, fostering dependencies and influence in key Indo-Pacific states. However, the implementation of BRI also encounters resistance in the form of debt-trap diplomacy allegations, environmental critiques, and counter-initiatives like the U.S.-led Indo-Pacific Strategy. The article concludes that the BRI is central to China’s vision of a Sinocentric order, signaling a shift from unipolar to multipolar geopolitical competition in the Indo-Pacific.